STRATEGI KLASTER INDUSTRI MENGHADAPI PASAR GLOBAL - Andriyanto, Irsad; Nurjanah, Nurjanah (Universitas Islam Negeri Sunan Kudus, 2015)
ASEAN Economic Community (AEC) 2015 can bring both positive and negative impact on MSMEs. To deal with any negative impacts,SMEs need for strategies to exist and continue growing. One such strategy is the cluster approach. This approach is done by groupingthe core industries that are interconnected, both supporting industries (supporting industries), industries related (related industries), supporting services, economic infrastructure, research, training, education, information infrastructure, technology infrastructure, natural resources, and any related institutions. Cluster is also a way to set some economic development activities. Based on the result, Strategies to Increase Industry Competitiveness in Facing ASEAN Economic Community (AEC) is done by: 1. The use of core competencies in seeking to improve the competitiveness clusters. And 2. Creating their competitive advantage cluster based on RBV (Resources Based Value) approach.